Pendekatan Preventif Tokoh Agama terhadap Remaja Berperilaku Negatif di Kelurahan Kaliawi Bandar Lampung - Makmun, Fariza (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This study aims to understand and analyze the prevention strategies carried out by religious leaders in dealing with deviant behavior in adolescents in Kaliawi Village, Tanjung Karang Pusat District, Bandar Lampung City. The phenomenon of juvenile delinquency and social deviation is a quite disturbing issue, especially in urban areas. In this context, religious leaders have an important role as agents of moral change through a da'wah approach, which focuses on the formation of character and spiritual values ​​in adolescents. The method used in this study is qualitative, with data collection techniques in the form of in-depth interviews, field observations, and documentation studies. The research findings show that religious leaders in the area apply various preventive approaches, such as religious study activities, group discussions, and spiritual guidance to strengthen adolescents' religious understanding. They also involve the role of families and the surrounding community to create a conducive environment for better behavioral change. The main factors that cause negative behavior in adolescents include dropping out of school triggered by economic problems, lack of education, and deviant behavior in adolescents themselves. To prevent juvenile delinquency, religious leaders apply an approach that includes understanding of general juvenile problems as an effort for ongoing development, as well as education that focuses not only on skills, but also on personality formation through religious teachings, ethics, and morals. In addition, they also provide facilities and create an atmosphere that supports healthy adolescent development and provide guidance aimed at forming a better young generation in the future.